2004
DOI: 10.1002/ptr.1428
|View full text |Cite
|
Sign up to set email alerts
|

In vitro anti‐tyrosinase activity of 5‐(hydroxymethyl)‐2‐furfural isolated from Dictyophora indusiata

Abstract: The inhibition of mushroom tyrosinase by methanolic extract of Dictyophora indusiata was evaluated and the bioactive component was characterized and identified as 5-(hydroxymethyl)-2-furfural (HMF) by chromatographic and spectroscopic means. Kinetic studies revealed it to be a noncompetitive inhibitor for the oxidation of L-DOPA. On the basis of these findings some related analogues were also tested for their anti-tyrosinase activity, in order to gain more insight into structure and activity relationship among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 20 publications
0
37
0
4
Order By: Relevance
“…It was shown that HMF present in the extract was responsible for the inhibitory effect, and the kinetic studies revealed it to be a non--competitive inhibitor for the oxidation of L-DOPA [Sharma et al, 2004]. HMF was also identified as the active component in the hot water extracts of Lycium Chinese.…”
Section: Carcinogenic Toxic and Mutagenic Activities Of Hmfmentioning
confidence: 99%
“…It was shown that HMF present in the extract was responsible for the inhibitory effect, and the kinetic studies revealed it to be a non--competitive inhibitor for the oxidation of L-DOPA [Sharma et al, 2004]. HMF was also identified as the active component in the hot water extracts of Lycium Chinese.…”
Section: Carcinogenic Toxic and Mutagenic Activities Of Hmfmentioning
confidence: 99%
“…(Bakshi & Mandal 2006). Tyrosinase inhibitor (5-hydroxymethyl-2-furfural) could serve as skin depigmenting and lightening agent (Sharma et al 2004;Parvez et al 2006). Two glucans were isolated from P. (Hara et al 1982;Wang et al 2009) and fucomannogalactan (glycan) has been considered an immunomodulator (Wasser 2002;Zhang et al 2007).…”
Section: Dictyophora Merulinamentioning
confidence: 99%
“…Логично, что «переброска сил» гриба с пути конверсии D-фруктозы в D-маннит способствует активизации альтернативного пути «фруктоза → 5-гидроксиметил-2-фуральдегид». Особенно если учесть, что последний ингибиру-ет фермент тирозиназу, ответственную за синтез грибного пигмента меланина, то есть служит ингибитором меланиногенеза [17].…”
Section: результаты и их обсуждениеunclassified